Pengaruh Media Fun Learning Card Terhadap Hasil Belajar Peserta Didik Kelas XI SMAN 21 Surabaya - Sabda Bagus Baswara (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Education plays an important role in shaping learners' competencies, including cognitive, affective and psychomotor aspects to face the challenges of the times. In Indonesia, education should look at holistic aspects that include character development, life skills and social abilities as mandated in Law No. 20/2003. However, challenges in classroom management and learning boredom often become obstacles. For this reason, innovative approaches are needed, such as the use of interactive learning media. This study aims to examine the effect of using Fun Learning Card media on the learning outcomes of grade XI students at SMA Negeri 21 Surabaya. This media is expected to significantly increase student participation and understanding, overcome boredom, and create more meaningful learning. By using descriptive statistical analysis techniques, standard deviation, and learning outcome categories, the following results were found before using the learning media in cycle 1 with an average score of 49.6. The score was obtained from the lowest score of 35 and the highest score of 70, then also obtained a standard deviation score (P) of 10.2. In cycle 2 using Fun Learning Card media, the highest score was 97 while the lowest score was 76 with an average score of 85.4 and a standard deviation of 6.3.